Antidiabetic and Regenerative effects of alcoholic corm extract of Nervilia aragoana Gaud. in NIDDM rats - EK Dilipkumar; GR Janardhana (International Journal of Phytomedicine, 2013)
Nervilia aragoana Gaud. (Orchidaceae) has long been used in the antidiabetic medicinal preparations of traditional healers of Wayanad (Kerala), but antidiabetic and regenerative potential of the plant remain unravelled. The aim of the present study was to investigate the recuperative and regenerative potential of alcoholic stem extract of Nervilia aragoana Gaud. on streptozotocin-nicotinamide induced type 2 diabetic models. Administration of 5mg/kg of plant extract, blood glucose levels of the NIDDM rats showed 65.91 and 76.58 % decrease in the blood glucose levels on 0 and day 30 days respectively. Damages caused to the kidney tissue were negligible or not seen. Serum urea and creatinine levels showed 65.00 % and 71.00% decrease on day 30. LPP levels of kidney and pancreas showed 76.47 % and 74.19% decrease respectively. These results demonstrate significant antidiabetic and regenerative potential of the Nervilia aragoana Gaud. justifying the use of plant in the indigenous system of medicine. Isolation and characterisation of the compound(s) playing pivotal role in the cure would open new vistas in the therapy of type 2 diabetes.